Strengthening Islamic Financial Literacy Education for Millennial Generation - Sufyati HS (AL-ISHLAH: Jurnal Pendidikan, 2021)
Indonesia is one of the countries with the largest Muslim population in the world. In this era of disruption, millennials are the generation that plays an essential role in contributing to government programs. One of the programs launched is the development of national Islamic finance. Financial literacy is a basic need for everyone, including the millennial generation, to avoid financial problems. The financial sector has been effective in encouraging economic development, both in terms of the ability and accuracy of spending, business financing, and the accuracy of savings and investment choices. This study aims to determine the impact of Strengthening Islamic Financial Literacy Education on the Millennial Generation. This study uses a quantitative approach with the Wilcoxon test technique. The population in this study were students majoring in management at UPN Veteran University, with a sample of 88 respondents using the purposive sampling technique. The results showed differences in students representing the millennial generation after the Islamic financial literacy education training was carried out; this was indicated by a sign of 0.037 or less than 0.05. In the implementation of literacy, there has also been a change between before and after the provision of Islamic financial literacy training to students. This study also revealed that universities play an essential role in providing education to students in understanding Islamic financial literacy.